2015
DOI: 10.1177/0017896915599416
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perceptions of illness and health: An analysis of drawings

Abstract: Objective: The purpose of this study was to explore possible age differences in children’s perceptions of illness and health and to what extent these differ from adults’ perceptions. Design: Cross-sectional design. Setting: Selected nursery and primary schools in Greece. Method: The sample consisted of 347 children aged 5–11 years and 114 adults – as a comparison group. Each participant was asked to create two drawings, depicting illness and health respectively, and to give an explanatory title for each. Drawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
6
22
0
7
Order By: Relevance
“…The youngest respondents had the highest amount of wrong ideas about diseases and the oldest ones had fewer numbers of wrong ideas. Similar results could be found in the study of Mouratidi, Bonoti, and Leondari (2015) and also Myant, and Williams (2005). Pidgeon (1985) also stated that children's knowledge of specific illnesses increases significantly during the school-age years.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The youngest respondents had the highest amount of wrong ideas about diseases and the oldest ones had fewer numbers of wrong ideas. Similar results could be found in the study of Mouratidi, Bonoti, and Leondari (2015) and also Myant, and Williams (2005). Pidgeon (1985) also stated that children's knowledge of specific illnesses increases significantly during the school-age years.…”
Section: Discussionsupporting
confidence: 72%
“…In addition to the environment, children also mentioned the following causes of illness: lack of hygiene, sneezing of strangers, eating at McDonald's, overly sweet and savory meals. Mouratidi, Bonoti, and Leondari (2015) found that older pupils have better concepts about illness and health than younger pupils, while the youngest pupils had difficulties with representing the two concepts clearly. Piko and Bak (2006) demonstrated statistically insignificant difference between boys and girls regarding concepts of illness and that children's past experiences (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Connected with these ideas, Madden and Liang's study [25] reports that interactions among livings things become more frequent in young children's verbal and graphical expression as a consequence of their involvement in learning activities aiming to strengthen a relational perspective of nature. This means that the additional level of complexity that entails recognising the environment in terms of the interactions between living things is within the reach of young children before the age of eight.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a study that involves 35 preschool children's drawings, Lauren Madden and Jennifer Liang [25] provide evidence that the children express interactions between plants and animals in their depictions of nature. Furthermore, this study leads to the conclusion that these illustrations become more frequent after the children are involved in specific educational interventions to promote a better understanding of the role that trees have as creatures' habitats.…”
Section: Introductionmentioning
confidence: 99%
“…22,23,25,26 Çeşitli araştırmacılar Piget Teorisi'ni, çocuk-larda sağlık ve hastalık kavramları anlayışını incelemek üzere adapte etmiş ve gruplara göre yanıtları incelemişlerdir. 24,27,28 Küçük çocuklar, ağrı ve hastalık nedenleri ile ilgili ben merkezci ve büyülü, genel olarak medikal ve kültürel kavramlar içer-meyen, daha somut, "o an"a odaklı ve semptoma özgü açıklamalar yapmaya daha yatkın bulunmuş-lardır. 26,[29][30][31] Bibace ve Walsh, bu evrede olaycılık ve bulaşma içerikli açıklamalarda bulunulabileceğini belirtmektedirler.…”
Section: Okul öNcesi̇ çOcuklarda Ağri Ve Değerlendi̇rmesi̇ (3-7 Yaş)unclassified